2020
DOI: 10.1177/0030727020960165
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable rice production in the Mekong River Delta: Factors influencing farmers’ adoption of the integrated technology package “One Must Do, Five Reductions” (1M5R)

Abstract: Over the last few decades Vietnam has benefited from a rapid intensification of rice production ensuing high yields and economic gains. However, this has led to environmental degradation and adverse health effects. As a result, complex sustainable rice farming packages have been introduced but adoption still appears to be low. The present study aimed to investigate the factors affecting the adoption of sustainable rice farming practices combined in the national program “One Must Do, Five Reductions” (1M5R). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…Existing studies on the factors influencing the adoption of EAT by farmers have found that farmers' intention to adopt is influenced by a combination of subjective and objective factors. Objective factors include social learning and social networks, socioeconomic factors, price factors, immediate conditions and social climate, green technology adoption risks and government regulation, the share of farmers' income in total household income and economic benefits of ecological production technologies, technological environment, plot elements and access to raw materials (Connor et al, 2021;Li et al, 2021;Ruzzante et al, 2021;Sapbamrer and Thammachai, 2021;Shang et al, 2021;Wang et al, 2021). The subjective factors are ecological compensation perception and ecological environment perception, ecological compensation intention, environmental crisis awareness, ecological environment improvement effect, and ecological environment policy perception (Savari et al, 2021;Tama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on the factors influencing the adoption of EAT by farmers have found that farmers' intention to adopt is influenced by a combination of subjective and objective factors. Objective factors include social learning and social networks, socioeconomic factors, price factors, immediate conditions and social climate, green technology adoption risks and government regulation, the share of farmers' income in total household income and economic benefits of ecological production technologies, technological environment, plot elements and access to raw materials (Connor et al, 2021;Li et al, 2021;Ruzzante et al, 2021;Sapbamrer and Thammachai, 2021;Shang et al, 2021;Wang et al, 2021). The subjective factors are ecological compensation perception and ecological environment perception, ecological compensation intention, environmental crisis awareness, ecological environment improvement effect, and ecological environment policy perception (Savari et al, 2021;Tama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, location determines the type of raw materials used in production as a result of social class and purchasing ability, hence the smaller MSMEs will go for what they can afford as opposed to what is currently trending as the best (Caswell et al, 2013). Larger enterprises are attributed to better packaging materials, frequency of operations and better markets as opposed to smaller MSMEs whose customers are majorly locals consisting of street passersby (Connor et al, 2020;Mukanyandwi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gender and age are the origin factors for the contradiction between the adoption willingness and behavior of rural households (Yu et al, 2017). Education level is one of the main driving forces for the adoption behavior of rural households, but farmers with shorter or longer education years are unwilling to adopt new technologies (Luo et al, 2013;Connor et al, 2020). Cognition, value and attitude have an important impact on the adoption behavior of rural households (Gao, 2010;Jha et al, 2019).…”
Section: Adoption Behavior Of Rural Householdsmentioning
confidence: 99%
“…( 2) Household characteristics are one of the crucial factors that influence the adoption behavior of farmers, mainly including the proportion of agricultural income (Han & Yang, 2011;Guo & Hou, 2012), part-time householder (Zhao & Cai, 2012), the status of household durable assets (Luo et al, 2013) and household wealth (Jha et al, 2019). (3) Technical characteristics include technical guidance, implementation convenience, technical understanding ability and technology availability which have a significant positive impact on the adoption behavior of rural households (Han & Yang, 2011;Connor et al, 2020). However, the factors closely related to the technology show an increasing trend with the increase of non-agricultural income.…”
Section: Adoption Behavior Of Rural Householdsmentioning
confidence: 99%